Kajian Multikulturalisme dan Kaitannya dengan Kerukunan - M. Amin Nurdin (Refleksi, 2019)
Multiculturalism is the best alternative model that can offer a policy of interaction and bilateral enrichment to the dominant culture and the minority culture concerned. While religious pluralism offers a policy that is analogous with integration policy. Religion becomes a resource for value and norms which can influence the way of thinking, mental attitude, and behaviour of the dominant culture and minority culture in the society. Multiculturalism tries to gradually change all the minority cultures to be eventually fit in the batter within the dominant culture without seeing the values and norms of the religions followed. Similar with the liberal-democracy state, ethnic conflict in Indonesia empties into the conflict of local ethnics versus the incoming ethnic (immigrant). Impact of this conflict has caused social crisis and economic crash and the migrant’s ethnic environment and eviction from the home where they have lived in so far. Therefore, multiculturalism ideology could become a solution to create harmonious society with fairness and equality without regard to any socio-cultural background.